2007
DOI: 10.1002/chem.200700805
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Dependent Interconversions between RhI, RhII, and RhIII Complexes of an Aryl–Monophosphine Ligand

Abstract: Reaction of the aryl-monophosphine ligand alpha(2)-(diisopropylphosphino)isodurene (1) with the Rh(I) precursor [Rh(coe)(2)(acetone)(2)]BF(4) (coe=cyclooctene) in different solvents yielded complexes of all three common oxidation states of rhodium, depending on the solvent used. When the reaction was carried out in methanol a cyclometalated, solvent-stabilized Rh(III) alkyl-hydride complex (2) was obtained. However, when the reaction was carried out in acetone or dichloromethane a dinuclear eta(6)-arene Rh(II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 40 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…The structure of 3d″ was determined by X-ray crystallography (Figure ). The 31 P­{ 1 H} NMR spectrum of 3d″ shows a two-bond P–P coupling constant of 462 Hz, which is within the range of common 2 J PP values between two trans phosphorus atoms. , Similar C–H activations of the methyl of mesityl or mesitylene by late-transition-metal complexes has been reported. , The oxidative addition product, ( Mes PNP)­Rh­(Me)­(I) 2 ( 3d ), could be observed by NMR spectroscopy, but attempts to isolate it were not successful due to the conversion to 3d″ and methane. The 1 H NMR spectrum of the reaction between 3c and MeI reveals a triplet of doublets at 1.59 ppm assigned to the Rh–CH 3 group of ( Mes PNP)­Rh­(Me)­(I) 2 ( 3d ).…”
Section: Resultsmentioning
confidence: 59%
“…The structure of 3d″ was determined by X-ray crystallography (Figure ). The 31 P­{ 1 H} NMR spectrum of 3d″ shows a two-bond P–P coupling constant of 462 Hz, which is within the range of common 2 J PP values between two trans phosphorus atoms. , Similar C–H activations of the methyl of mesityl or mesitylene by late-transition-metal complexes has been reported. , The oxidative addition product, ( Mes PNP)­Rh­(Me)­(I) 2 ( 3d ), could be observed by NMR spectroscopy, but attempts to isolate it were not successful due to the conversion to 3d″ and methane. The 1 H NMR spectrum of the reaction between 3c and MeI reveals a triplet of doublets at 1.59 ppm assigned to the Rh–CH 3 group of ( Mes PNP)­Rh­(Me)­(I) 2 ( 3d ).…”
Section: Resultsmentioning
confidence: 59%
“…This trend can be attributed to the higher basicity of the t Bu groups, which results in more back-bonding to the dinitrogen ligand, with a corresponding weakening of the N−N bond. While several PCP-based dinitrogen complexes are known, only a small number of POCOP-based complexes have been reported. , …”
Section: Resultsmentioning
confidence: 99%
“…The most common mononuclear Rh(II) complexes are porphyrin complexes. , Stable pincer-type Rh(II) bis(oxazoline) monomeric complexes were reported by Bergman and Tilley . Recently, monomeric Rh(II) PNP-type complexes, as well as PC-type Rh(II) complexes, were prepared in our group. To the best of our knowledge, Rh(II) complexes of the common PCP pincer type systems are not known.…”
Section: Introductionmentioning
confidence: 99%
“…First, the phosphine donor group in 1 has one benzyl and two isopropyl substituents, which makes it essentially identical, both sterically and electronically, to the phosphine donors of the abovementioned PCP ligand, which has been shown to undergo CO‐promoted CH oxidative addition 3. Second, previous work has shown that reaction of two equivalents of ligand 1 with the Rh I precursor [Rh(acetone) 2 (coe) 2 ]BF 4 (coe=cyclooctene), as shown in Scheme a, leads to the cyclometalated Rh III complex 2 ,5c the very structure of which, with its trans ‐positioned phosphine moieties, makes it a potential precursor for the preparation of a cationic trans ‐dicarbonyl bisphosphine Rh I complex. Indeed, we have found that when complex 2 is treated with excess CO, facile CH reductive elimination takes places to afford the cationic trans ‐dicarbonyl bisphosphine Rh I complex 3 (Scheme a) 6…”
Section: Resultsmentioning
confidence: 99%
“…The complex [Rh(acetone) 2 (coe) 2 ]BF 4 was prepared according to a literature procedure with appropriate modifications 40. Ligand 1 ,5c complex 2 ,5c and ligand 5 41 were prepared according to previously reported procedures. All solvents were reagent grade or better.…”
Section: Methodsmentioning
confidence: 99%